2020
DOI: 10.3390/ani10091516
|View full text |Cite
|
Sign up to set email alerts
|

Temperament in Domestic Cats: A Review of Proximate Mechanisms, Methods of Assessment, Its Effects on Human—Cat Relationships, and One Welfare

Abstract: Temperament can be defined as interindividual differences in behavior that are stable over time and in different contexts. The terms ‘personality’, ‘coping styles’, and ‘behavioral syndromes’ have also been used to describe these interindividual differences. In this review, the main aspects of cat temperament research are summarized and discussed, based on 43 original research papers published between 1986 and 2020. We aimed to present current advances in cat temperament research and identify potential gaps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 131 publications
(420 reference statements)
0
10
0
Order By: Relevance
“…Previous feline personality studies have found one to six main personality dimensions [2], which often somewhat differ between studies. In an extensive review about feline personality, Travnik and colleagues [2] named some of the dimensions as friendliness, aggressiveness, boldness, openness, activity, impulsiveness and dominance. Previous studies have labeled these traits variably.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Previous feline personality studies have found one to six main personality dimensions [2], which often somewhat differ between studies. In an extensive review about feline personality, Travnik and colleagues [2] named some of the dimensions as friendliness, aggressiveness, boldness, openness, activity, impulsiveness and dominance. Previous studies have labeled these traits variably.…”
Section: Introductionmentioning
confidence: 76%
“…Personality can be defined as interindividual differences in behavior which are stable over time and in distinct contexts [1]. Personality is influenced by genetics, the environment and their interactions [2]. Personality differences between individuals have been found in several species, including domestic cats [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations